2020
DOI: 10.1002/agg2.20023
|View full text |Cite
|
Sign up to set email alerts
|

Does potentially mineralizable nitrogen predict maize yield in newly cropped soil?

Abstract: Fallow soils converted to crop use have unpredictable soil organic nitrogen (SON) availability during the growing season, which incentivizes over‐applying fertilizer N by way of compensation. Potentially mineralizable nitrogen (PMN) is a soil health indicator, and its increase is a management strategy to meet crop N demands. How well does PMN predict yield in transition, periods from fallow to crop, especially when conservation practices are imposed simultaneously? In a short‐term study, conducted in Madison C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Cover cropping entails using vegetative crops (e.g., mixes of legumes and grasses) to prevent soil erosion, suppress weeds, and provide nitrogen to subsequent cash crops [84]. Cover crops have the potential to sequester carbon below ground, but the amount and type of residues produced by plants place a strong control on SOC storage [85]. Studies have shown higher rates of soil carbon sequestration on former croplands when planted with diverse mixtures of grass and legume [86,87].…”
Section: Understanding Soil Organic Carbon-its Loss Protection and Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cover cropping entails using vegetative crops (e.g., mixes of legumes and grasses) to prevent soil erosion, suppress weeds, and provide nitrogen to subsequent cash crops [84]. Cover crops have the potential to sequester carbon below ground, but the amount and type of residues produced by plants place a strong control on SOC storage [85]. Studies have shown higher rates of soil carbon sequestration on former croplands when planted with diverse mixtures of grass and legume [86,87].…”
Section: Understanding Soil Organic Carbon-its Loss Protection and Ac...mentioning
confidence: 99%
“…Over the past two decades, advances in soil conservation practices, cover cropping, and other improved soil amendments have demonstrated the potential to improve degraded soils, especially of marginal lands. However, as recent reports have noted, these exciting advances in knowledge have not widely penetrated farmers' practices [82,84,85]. While there are some exemplary programs (e.g., NRCS cover crop initiatives in the United States), the wide-scale changes needed to bolster wider adoption have yet to be materialized [107].…”
Section: Training and Preparing The New Agricultural Work Forcementioning
confidence: 99%